Attitudes, Beliefs, and Responses to Stalking: A Law Enforcement Perspective - Banner, Jessica L. (East Carolina University, 2013)
Approximately 3.4 million adults are stalked annually according to victim surveys, however this is not reflected in law enforcement data of those charged or convicted with stalking. Only 10.3% to 55% of stalking incidents are reported (Baum, Catalano, Rand, & Rose, 2009; Bjerregard, 2000; Tjaden & Thoennes, 1998) and rates of arrest, prosecution, and conviction of stalking offenders are even lower (Jordan et al. 2003; Storey & Hart, 2011; Tjaden & Thoennes, 1998). The current study looked to law enforcement to identify their beliefs about stalking which may impact the rates of formal legal action taken in stalking cases. Law enforcement responses were compared to a comparable group of victim advocates. Through various factor analyses and correlations, we found that participants who endorsed stalking myths reported using fewer informal helping strategies and found that characteristics of the victim and offender’s relationship was a substantial obstacle to handling stalking cases. Also, law enforcement officers gave more credit to stalking myths than did victim advocates even though their level of knowledge accuracy was very similar. No relationship was found between stalking knowledge accuracy and any criterion variable for either subpopulation group. Law enforcement officers and victim advocates both identified having difficulty determining what constituted stalking and how best to assess each situation implying that while trainings such as domestic violence may generalize to stalking, specialized stalking training is still warranted in order for officers to feel prepared to handle stalking cases.
Keywords: Stalking myths; Stalking; Law enforcement